Genetic Variants of MicroRNA and DROSHA Genes in Association With the Risk of Tuberculosis in the Amazon Population - Leal, Diana Feio da Veiga Borges; Santana da Silva, Mayara Natália; Pastana, Lucas Favacho; Fernandes, Marianne Rodrigues; Athayde, Aidalucy do Socorro Costa de; Fernandes Porchera, Débora Christina Ricardo; Silva, Cleonardo Augusto da; Modesto, Antônio André Conde; De Assumpcão, Paulo Pimentel; Santos, Sidney Emanuel Batista dos; Santos, Ney Pereira Carneiro dos (Frontiers in Genetics, 2022)
Tuberculosis (TB) is a chronic infection caused by Mycobacterium tuberculosis (Mtb) with high incidence and mortality. Studies reported that host genetic variants might be associated with the risk of tuberculosis. The aim of this study was to perform an association study between 26 single nucleotide polymorphisms (SNPs) and tuberculosis and evaluate whether these SNPs may confer risk factor to tuberculosis in Amazon population. This case-control study was conducted on 190 individuals with active TB and 176 healthy controls. Genotyping was performed using TaqMan Open Array Genotyping. Ancestry informative markers were used to estimate the ancestral proportions of the individuals in case and control group. The results indicated that SNPs rs10035440 (DROSHA), rs7372209 (miR26-a1), rs1834306 (miR100), rs4919510 (miR608), rs10739971 (pri-let-7a-1) were signiﬁcantly associated with high risk and rs3746444 (miR499) and rs6505162 (miR423), with low risk of developing tuberculosis in Amazon population. Our study concluded that seven miRNA polymorphisms were associated with tuberculosis. Our study contributes to a better understanding on TB pathogenesis and may promote the development of new diagnostic tools against M. tuberculosis infection.